Pengaruh Tatakelola Terhadap Nilai Perusahaan Perbankan: ROA Dan NPL Sebagai Mediasi - La Ode Sumail, Lisa Dentika, Syamsul Ridjal, (Jurnal Ekonomi, 2021)
This study attempts to investigate the effect of governance on firm value mediated by financial performance and risk of banking firms on the IDX. The sampling technique uses 46 saturated samples and data sources from the 2017-2020 financial statements so that the number of observations is 184. This study finds that bank governance can encourage an increase in firm value. Governance has a positive effect on ROA but has a negative effect on NPL. ROA has a positive effect on PBV and NPL has a negative effect on PBV. Governance has a positive and significant effect on PBV mediated by ROA and governance has a negative and significant effect on PBV mediated by NPL. Therefore, the role of ROA and NPL as partial mediation (partial mediation).